Utilising an anilido-imino ligand to stabilise zinc-phosphanide complexes: reactivity and fluorescent properties. Issue 23 (23rd April 2019) - Webb, Dylan; Fulton, J. Robin
Abstract : Anilido-imino-based ligands have been used to generate new zinc complexes, including rare zinc phosphanide and phosphinodichalcogenoate complexes. The fluorescence intensity of these compounds is highly dependent upon the non-ancillary ligand. Abstract : A series of zinc complexes bearing the anilido-imino ligand [( o -C6 H4 {N(C6 H3 i Pr2 )}{C(CH3 ) = NC6 H3 i Pr2 })] [(L Dipp )ZnX] has been generated. This includes two amide derivatives, [(L Dipp )Zn(N{SiMe3 }2 )] and [(L Dipp )Zn(NHDipp)] and two phosphanide derivatives, [(L Dipp )ZnPCy2 ] and [(L Dipp )ZnPPh2 ]. The chemistry of the phosphanide complexes towards chalcogens was examined, with sulfur, selenium and tellurium oxidising the phosphorus centre of the dicylohexylphosphanide complex [(L Dipp )ZnPCy2 ] to form [(L Dipp )Zn(E)2 PCy2 ] (E = S, Se, Te). Addition of tellurium to the diphenylphosphanide complex [(L Dipp )ZnPPh2 ] results in formation of Ph2 PPPh2 and [(L Dipp )ZnTeZn(L Dipp )]. The absorption and emission properties of these complexes was examined and the quantum yields are highly dependent upon the non-ancillary ligand X.